Intercultural Communication Barriers Between Expatriate Management and Local Managers: A Case Study of Bali Garden Beach Resort - Mertisari, Miranti; Tebe, Tesayunidia; Rosana, Anita (Jurnal Indonesia Sosial Sains, 2026)
Globalization and the increasing involvement of cross-national actors in the hospitality industry have created multicultural work environments that require effective intercultural communication. Differences in cultural backgrounds between expatriate management and local employees may generate communication barriers that affect organizational effectiveness. This study aims to explain the forms of intercultural communication barriers that occur between expatriate management and local staff at Bali Garden Beach Resort. The study adopts a qualitative approach using a case study method based on Yin’s case study design. Data were collected through in-depth interviews with expatriate and local informants and were analyzed using Edward T. Hall’s Intercultural Communication Theory, particularly the concepts of high-context and low-context culture. The findings indicate that intercultural communication barriers arise from differences in message delivery styles, interpretations of verbal and nonverbal communication, perceptions of hierarchy, as well as orientations toward time and work professionalism. These cultural differences are often not recognized as cultural issues but are instead perceived as individual attitude or performance problems. This study highlights the importance of strategically managing intercultural communication in multicultural hospitality organizations.